2015
DOI: 10.1111/jnu.12157
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Experience Associated With Immunosuppressive Medications in Chinese Kidney Transplant Recipients

Abstract: Understanding symptom experience of immunosuppressive medications is of importance for healthcare providers to offer sophisticated education and develop strategies to improve quality of life and medication adherence during follow-up post-transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
2
26
0
3
Order By: Relevance
“…have demonstrated that KTR with low adherence to immunosuppression had a significantly higher occurrence and distress of symptoms than patients with high or medium adherence after adjusting for a number of covariates and that the most common symptom both in terms of occurrence (96.4%) and distress (91.1%) among poorly adherent KT recipients was tiredness. Similarly, a large Chinese study has shown that high blood pressure, hair loss, and tiredness were the three most distressing symptoms occurring in KTR and negatively associated with poor adherence to the use of immunosuppressive medications . This is an important finding considering that poor adherence to immunosuppressive agents increases the risk of rejection and mortality.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…have demonstrated that KTR with low adherence to immunosuppression had a significantly higher occurrence and distress of symptoms than patients with high or medium adherence after adjusting for a number of covariates and that the most common symptom both in terms of occurrence (96.4%) and distress (91.1%) among poorly adherent KT recipients was tiredness. Similarly, a large Chinese study has shown that high blood pressure, hair loss, and tiredness were the three most distressing symptoms occurring in KTR and negatively associated with poor adherence to the use of immunosuppressive medications . This is an important finding considering that poor adherence to immunosuppressive agents increases the risk of rejection and mortality.…”
Section: Methodsmentioning
confidence: 90%
“…Chinese study has shown that high blood pressure, hair loss, and tiredness were the three most distressing symptoms occurring in KTR and negatively associated with poor adherence to the use of immunosuppressive medications. 33 This is an important finding considering that…”
Section: Effects Of Fatigue In Ktrmentioning
confidence: 86%
“…However, some surveys have indicated that renal transplant recipients experienced some symptoms related to primary end-stage renal disease, postoperative complications, and immunosuppressive therapy (Lee et al, 2015;Teng et al, 2015). Afshar et al (2012) reported that the symptom burden of renal transplant recipients is high, with a mean of seven symptoms (SD 5.2, range of 0-22).…”
Section: Introductionmentioning
confidence: 99%
“…The MTSOSD-59R has been validated in English, Dutch, and Turkish and translated, without validation, into Hindi, Spanish, French, German, and Korean [ 6 ]. Its use has also been recommended for organ transplant patients in other cultures [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%